Harnessing the Defects at Hetero‐Interface of Transition Metal Compounds for Advanced Charge Storage: A Review. Issue 9 (16th June 2022) - Li, Jin; Yang, Hongye; Wu, Jianghua; Sun, Shuo; Zhai, Teng; Xia, Hui
Abstract : The ability of transition metal compounds (TMCs; e.g., transition metal oxides, transition metal dichalcogenides) to achieve maximum energy and power density is undermined by their marginal electrical and ionic conductivity. There has been rapidly growing interest in a paradigm enabled by the construction of heterostructured TMCs over the past decades because it can increase the charge transport and storage capabilities of TMC‐based electrodes. The introduction of defects is a critical tool that allows the manipulation of heterostructures by altering the electronic structure and stress field. In this way, the electrochemical performance of the material can be optimized. Herein, recent progress in the development of heterostructured TMCs from the perspective of defects is comprehensively discussed. It is emphasized the mechanisms by which defects influence the electrochemical performance of heterostructures and effective strategies to incorporate the 0D to 2D defects (vacancies, elemental doping, lateral hetero‐interface, lattice mismatch, etc.) around the hetero‐interface, which is a focus that differs from previous reviews of heterostructured TMCs. Related problems and future directions in the defect chemistry of heterostructured TMCs are also discussed. This review highlights the significance of defects for guiding the rational design of TMC electrodes for use in advanced energy storage devices. Abstract : This review highlights the important role of introducing defects around the hetero‐interface when designing high‐performance chemically bonded heterostructures and van der Waals heterostructures, (vdWHs) with a focus on modulating the charge misdistribution and stress field at the hetero‐interface. Some strategies to modify hetero‐interfaces through 0D to 2D defects (oxygen vacancies, elemental doping, lateral hetero‐interface, lattice mismatch, etc.) are also systematically summarized.